Synthesis and thermal conductivities of ZnIn2Te4 and CdIn2Te4 with defect-chalcopyrite structure - Suriwong T. (2014)
ZnIn2Te4 and CdIn2Te4 have a defect-chalcopyrite tetragonal crystal structure with structural vacancies. In order to investigate the effects of vacancies on the lattice thermal conductivity (κlat), single phase samples of ZnIn 2Te4 and CdIn2Te4 were synthesized and their κlat values were examined in the temperature range from room temperature to 850 K. The κlat data for ZnIn 2Te4 and CdIn2Te4 were compared with those of Zn- and Cd-series chalcopyrite compounds with no vacancies. The results revealed that the presence of vacancies alone in the defect-chalcopyrite structure does not result in effective phonon scattering. © 2011 Elsevier B.V. All rights reserved.